Residual Stress and Affected Layer in Disc Milling of Titanium Alloy. Issue 13 (2nd October 2016) - Xin, Hongmin; Shi, Yaoyao; Ning, Liqun; Zhao, Tao
Abstract : Disc milling is used in manufacturing, especially for difficult-to-machine material such as titanium alloy, because of its strong force and high machining efficiency. However, research on the cutting mechanism of the disc-milling technique is still lacking in the literature. In the present study, first, a disc-milling grooving experiment was designed and carried out to test the milling temperature correlated to the milling force for titanium alloy samples. After machining, residual stress, microstructure and microhardness were investigated. Residual compressive stress was found on the milling surface, which changes to tensile stress gradually with the increase of depth. The impact of cutting factors on residual stress was also analyzed numerically and the results showed that with the increase of speed of the mainshaft, the residual stress reduced gradually. For the factors of depth of cut and feed speed, increasing them had the opposite effects on residual stress. Next, the microstructures of lattice tensile deformation and lattice fracture were observed under different cutting conditions. The metallographic structure changed on increasing the milling temperature, progressing from an initial equiaxed microstructure to an α + β duplex microstructure, and then formed a lamellar microstructure later. The microhardness in the plastic deformation zone was also taken into account, which showed that the hardness increased under the combined effect of the milling temperature and force.